A study of the factors affecting rural library services in Malaysia/ Salasiah M. Said and Wan Ab. Kadir Wan Dollah - M. Said, Salasiah; Wan Dollah, Wan Ab. Kadir (Faculty of Information Management, Universiti Teknologi MARA, 2012)
This study aims at identifying factors affecting the rural library services in Malaysia. This study focused on the staff capabilities in conducting rural library services, use of collections and /CT services in rural libraries. There are several problems associated with the rural library services, such as lack of commitment among the library staff, inadequate resources needed by the community, out-of-date collections, services such as multimedia connection are scarce and there was a lack of awareness among the rural community on the benefits of using the Internet. The research employed a case study approach in 2 rural libraries in Selangor. The findings indicate that: (a) majority of the respondents agreed the staff capabilities in conducting rural library services (mean=4.40); {b) majority of the respondents agreed that rural library provides sufficient and suitable collections to the users (mean=4.28); and (c) majority of the respondents agreed that /CT services is sufficient and should be continued (mean=4.22). Recommendations were made on the need for the better improvement for the efficient and utilisation of rural library. Finally, the researchers propose directions for future research in the area of rural library services.